The Ethical Dimension of Managerial Leadership Two Illustrative Case Studies in TQM - Guillén, Manuel (Journal of business ethics, 2001)
In recent decades, Total Quality Management (TQM) has become an important phenomenon in the world of business, but the implications and scope of quality programs are quite different everywhere. Since different explanations have been given, most authors agree that management commitment and leadership are indispensable elements for a successful TQM implementation. Nevertheless, the study of the literature reflects a terminological confusion on this point. The authors of this paper argue that commitment and leadership are not synonymous terms.While committed managers may lead the process of quality using exclusively their formal authority, those who are leaders generate a kind of influence that goes further than that. This paper suggests a multidimensional perception of leadership and upholds that only by considering the ethical dimension of leadership, together with technical and psycho-emotive ones, it is possible to explain more accurately interpersonal influences beyond the scope of power. As an illustrative example of the importance of considering each dimensions, the authors present two case studies of TQM implementation.